Contribution of Fishermen’s Wives to Household Income in Kawal Village, Bintan Regency - Gita Pesona; Haidawati Haidawati; Fitria Ulfah (Politeknik Negeri Sambas, 2026)
Fisher households are coastal community groups that depend heavily on unpredictable marine catches, resulting in fluctuating household income. This condition encourages fishermen’s wives to participate in economic activities to help meet household needs. This study aimed to analyze the contribution of fishermen’s wives to household income in Kawal Urban Village, Bintan Regency. A quantitative descriptive method was employed, with purposive sampling used to select respondents. Data were analyzed by calculating total costs, total revenue, total income, and the percentage contribution of wives’ income to household income. The results showed that fishermen’s wives engaged in ten types of work: processed food seller, tailor, small-scale retailer, teacher, domestic helper, clothing reseller, fisher, religious teacher, babysitter, and food stall operator. Each occupation had different cost and income structures, resulting in varying contributions to household income. The highest average income was obtained from operating a food stall, while the lowest income came from low-capital service work. The percentage contribution of fishermen’s wives to household income ranged from 7.69% to 51.63%, with the highest contribution from the food stall business.